IoT based detergent level monitoring system / Farhan Danial Zamri - Zamri, Farhan Danial (2024)
Monitoring the detergent level in real life might be difficult, particularly in places where significant volumes of detergent are frequently used. It might be challenging to manage inventories and avoid wastage without a reliable and precise method to measure the detergent level. Inaccurate readings may additionally impact the ways the detergent is being pumped, which might damage the machines or delay the cleaning process. This thesis aims to design an IoT Based Detergent Level Monitoring system by using Arduino Wemos D1 R1. This thesis proposed a detergent level monitoring system by using IoT technology. The system is composed of an ultrasonic sensor that measures the detergent level, an Arduino Wemos D1 R1 microcontroller that controls the pump and processes sensor data, a keypad for user input, an LCD screen to display the detergent level and other system status, an LED indicator to alert the user of low detergent level, and Blynk app to remotely monitor the detergent level. Hence, by using an accurate and efficient monitoring system, businesses can ensure that they are using the optimal amount of detergent, thereby saving costs.